Cohabitation Attitudes and Behaviours of Undergraduate Students in Taraba State, Nigeria: The Mediating Role of Social Media and Peer Pressure - Saheed, Rahman O.; Seedat-Khan, Mariam (ABUAD Journal of Social and Management Sciences, 2024)
This study examines the impact of social-media and peer pressure on attitudes and behavior of undergraduate students towards cohabitation. The study sampled 1,970 undergraduate students from three universities in Taraba State, Nigeria. Data was collected with an online questionnaire. The study adopts social learning theory and Berger and Luckman’s social construction of reality. The data was analyzed using multiple regression and mediation analysis. The results reveal significant positive effects of attitudes towards cohabitation, social media use, and peer pressure on behaviours towards cohabitation. The finding revealed that a one-unit increase in attitudes towards cohabitation corresponds to a 0.41-unit increase in cohabitation behaviours. It also revealed that, a one-unit increase in social media use and peer pressure leads to a 0.21-unit and 0.25-unit increase, respectively, in cohabitation behaviours. Furthermore, the study shows that age negatively affects cohabitation behaviours, indicating a decrease in behaviours as age increases. The mediation analysis reveals that attitudes towards cohabitation significantly predict behaviors towards cohabitation (coefficient = 0.26 P <0.001). The study further revealed that social media use and peer pressure partially mediate the relationship between attitudes and behaviours towards cohabitation (0.19 (P< 0.001) with a 95% confidence interval of 0.14, 0.24). The study concludes that social media use and peer pressure play essential roles in shaping attitudes towards cohabitation and cohabiting behaviour among undergraduates in Taraba State.